Circulating Tumor Cell Kinetics and Morphology from the Liquid Biopsy Predict Disease Progression in Patients with Metastatic Colorectal Cancer Following Resection - Kolenčík, Drahomír; Narayan, Sachin; Thiele, Jana-Aletta; McKinley, Dillon; Gerdtsson, Anna Sandström; Welter, Lisa; Hošek, Petr; Ostašov, Pavel; Vyčítal, Ondřej; Brůha, Jan; Fiala, Ondřej; Šorejs, Ondřej; et al. (Cancers, 2022)
The liquid biopsy has the potential to improve current clinical practice in oncology by providing real-time personalized information about a patient's disease status and response to treatment. In this study, we evaluated 161 peripheral blood (PB) samples that were collected around surgical resection from 47 metastatic colorectal cancer (mCRC) patients using the High-Definition Single Cell Assay (HDSCA) workflow. In conjunction with the standard circulating tumor cell (CTC) enumeration, cellular morphology and kinetics between time-points of collection were considered in the survival analysis. CTCs, CTC-Apoptotic, and CTC clusters were found to indicate poor survival with an increase in cell count from pre-resection to post-resection. This study demonstrates that CTC subcategorization based on morphological differences leads to nuanced results between the subtypes, emphasizing the heterogeneity within the CTC classification. Furthermore, we show that factoring in the time-point of each blood collection is critical, both for its static enumeration and for the change in cell populations between draws. By integrating morphology and time-based analysis alongside standard CTC enumeration, liquid biopsy platforms can provide greater insight into the pathophysiology of mCRC by highlighting the complexity of the disease across a patient's treatment.